Pengaruh Kualitas Pengalaman, Kepercayaan dan Kepuasan terhadap Keterlibatan dan Loyalitas Pelanggan pada Pengguna E-Wallet - Natasya Aprilia Ningrum; Yuyus Yudistria (Yayasan Literasi Sains Indonesia, 2025)
Technological developments have driven innovation in payment systems through e-wallets, which facilitate cashless transactions and increase the popularity of services such as Gopay, Dana, ShopeePay, Ovo, and LinkAja in Indonesia, as well as encouraging service providers to create high value for customers, which in turn increases customer loyalty. This study analyzes the influence of experience quality, trust, and satisfaction on customer engagement and loyalty in the use of e-wallets. A quantitative study using the Structural Equations Model (SEM) method was conducted, focusing on e-wallet users. Data was collected through an online questionnaire using Google Forms with a purposive sampling method, resulting in 110 respondents. Data analysis was processed using SmartPLS4 software. The findings indicate that customer experience quality significantly influences customer trust and satisfaction, which in turn influence customer engagement, and ultimately, customer engagement, trust, and satisfaction positively impact customer loyalty. This study shows that customer experience quality has the greatest influence on trust, satisfaction, engagement, and loyalty toward e-wallets, so companies should prioritize ease of use, speed, security, and personalization of services